Penyusunan Laporan Keuangan CV. Surya Parama Arga Karya Menggunakan Microsoft Excel Sesuai Dengan SAK EMKM - Sutarti, Sutarti; Triandi, Triandi; Maulina, Lani (Jurnal Abdimas Dedikasi Kesatuan, 2025)
Financial reports are information about the financial position and performance of an entity that plays an important role in economic decision-making, especially for parties who do not have direct access to request special financial reports. The preparation of financial reports must be in accordance with applicable accounting standards, such as PSAK, SAK ETAP, SAK EMKM, and SAK Syariah. For micro, small, and medium enterprises (MSMEs), the preparation of financial reports is regulated in SAK EMKM, including for CV. Surya Parama Arga Karya, a micro-enterprise in the catering sector. This community service (PKM) activity aims to assist CV. Surya Parama Arga Karya in preparing financial reports based on SAK EMKM. The method used is qualitative with a descriptive approach. The data used consists of primary data obtained through observation and interviews, as well as secondary data sourced from related documents. Before the mentoring, the financial recording system of CV. Surya Parama Arga Karya was still done manually by only recording cash inflows from catering sales. The results of the PKM activity show that before the mentoring, CV. Surya Parama Arga Karya has not implemented financial recording in accordance with applicable standards. However, after mentoring, business actors succeeded in compiling financial reports using Microsoft Excel in accordance with the SAK EMKM standards. With this mentoring, it is hoped that CV. Surya Parama Arga Karya can implement recording and preparation of financial reports more systematically and sustainably in order to increase transparency and accountability of business finances.Keywords: financial reports, MSMEs, SAK EMKM, mentoring, accounting